Integrating Ecotheological Values in the Islamic Religious Education Curriculum: The Green Islamic Education Perspective in Karawang Secondary Schools - Taufik Mustofa; Nurhasan Nurhasan; Nur Aini Farida; Dwi Noviatul Zahra; Afif Nurseha (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The increasingly alarming global environmental crisis, accompanied by the complexity of ecological problems at the local level, demands innovation in educational practices, including in the context of Islamic Religious Education, in order to internalize ecological awareness based on spiritual values and religious ethics. This study aims to analyze the integration of ecotheological values into the PAI curriculum with the perspective of Green Islamic Education in secondary schools in Karawang Regency. This research used a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and document analysis, with source and method triangulation techniques to ensure data validity. The results showed that the integration of ecotheological values has been carried out through three main approaches, namely strengthening students' spiritual awareness of nature as a manifestation of God's power (ayat kauniyah), applying ecological ethics in learning and school activities, and developing real environmental-based actions such as greening programs, waste management, and community-based projects. Nevertheless, the integration has not been fully optimized because it still faces obstacles such as limited resources, lack of teacher training, and policy support that has not been maximized. This research emphasizes the importance of strengthening the capacity of PAI teachers, developing an adaptive curriculum, and supporting sustainability-based education policies. Thus, this research not only enriches the study of Islamic education and ecology, but also provides a conceptual and practical basis for the development of contextual, visionary, and sustainability-oriented PAI curriculum. This contribution emphasizes the significance of the role of Islamic education in forming a religious generation that has ecological awareness, environmental ethics, and a real commitment to the preservation of the earth as God's mandate.